Acute fluctuating neurological deficits after pulmonary vein isolation: unmasking a rare complication due to spontaneous spinal subdural bleeding: a case report. Issue 3 (5th July 2019) - Cioffi, Giacomo Maria; Regoli, François; Conte, Giulio; Auricchio, Angelo
Abstract: Background: Pulmonary vein isolation (PVI) is becoming the therapy of choice for symptomatic paroxysmal drug-refractory atrial fibrillation (AF). The most frequently reported complications are vascular complications (1.4%). Bleeding complications of the central nervous system have rarely been described. We report a case of spontaneous spinal bleed after PVI. Case summary: A 68-year-old woman with a 2-year history of highly symptomatic paroxysmal AF (EHRA 3) was referred for a PVI redo procedure. A high-density mapping showed pulmonary vein reconnection of all pulmonary veins successfully isolated by radiofrequency ablation. During the entire procedure, the patient had sinus rhythm with an ACT around 300 s. No intraprocedural and peri-procedural complications occurred. Four hours after haemostasis, the anticoagulation clotting time (ACT) was 110 s and rivaroxaban (20 mg) was reinitiated. In the following hours, the patient developed fluctuating neurological lower limb symptoms. A lumbar magnetic resonance imaging showed a subdural spinal haematic collection with an associated epidural component from L3 to S2 exerting compression over the dural sheath. A conservative treatment approach was adopted with progressive recovery of sensorial and motor deficits. After 5 months, the patient still presented residual lower limb motor deficits necessitating the support of a walking stick. Discussion: We describe the first case of a spontaneous spinal bleeding following PVI. Given the gradual diffusion of PVI to treat AF in more clinically complex patients with a larger range of comorbidities, particular consideration should be given to seek predisposing bleeding factors in order to assess the risk for neurological complications.